Design of an Enterprise Architecture for the Company Profile Using the TOGAF Method (Case Study: CV. Pertiwi Asri) - Dabar Hutabarat; Sintaria Sembiring (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2025)
This research is motivated by the need of CV. Pertiwi Asri, a company engaged in landscaping services, to improve the efficiency of its promotional processes, which have not been optimized through the use of information technology, resulting in limited market reach. To address this issue, the study designs an information system based on Enterprise Architecture using the TOGAF ADM (The Open Group Architecture Framework – Architecture Development Method) approach. The main objective of this research is to develop an enterprise architecture blueprint and design the user interface of a digital company profile information system that includes services, portfolios, and an online project proposal feature. The results of this study are expected to provide both strategic and technical guidance for CV. Pertiwi Asri in developing an integrated information system that aligns with business needs, thereby enhancing competitiveness and expanding market reach effectively.